(untitled) (مجلة البحوث الأكاديمية, 2021)
The current paper is to investigate the shortage problem of fresh water in Libya and to propose alternative solutions by renewable and sustainable energies. This problem is not only in Libya but it is one of the most serious social and environmental challenges facing many countries in the world, especially those countries which do not have natural resources or any types of energies. Although Libya is located in a dry and semi-arid region of Africa, it is very rich in conventional energy resources, mainly the oil, and renewable energies such as solar and wind energies. In addition to that it has about 1700 km border on sea, which is very helpful to establish many desalination plants either by conventional or renewable energies. Nowadays the shortage problem of water in Libya is solved partly by ground water resources and desalination plants which are not enough. In the other hand the quantity of oil is limited to a certain period of time with other environmental impacts of this resource Here, this paper is to study the water resources as well as conventional and energy situations in Libya and suggest the most appropriate solutions for today and future by combining solar and wind energies with desalination processes. This can be done by encouraging and supporting private and de-central solar desalination technologies and establishing central desalination units for high productivity by using solar thermal or electrical processes.